Topics in Heart Failure Management - Rescigno, Giuseppe; Firstenberg, Michael S. (IntechOpen, 2019)
This textbook represents a short update on original aspects of heart failure. It covers topics of heart failure management such as prevention, drug monitoring after heart transplant, and the critical care approach. There are also chapters on less common facets of this syndrome such as prevalence and features in a specific African region and the complexity of telemedicine in heart failure. In summary, it will be a valid adjunct to more exhaustive textbooks already available.